And If We Think About the Community with Rights?: Community Psychology, Rights and Public Policies. a Complex Relationship [¿ Si Pensamos la Comunidad Con Derechos? Psicología Comunitaria, Derechos y Políticas Públicas. Una Relación Compleja] - Winkler-Muller, M (Pontificia Universidad Javeriana, 2018)
This article presents results from the third stage of an investigation called "Ethics and Politics: Dimensions forgotten in Community Psychology?", where he reflects on the rights of communities participating in community interventions. A qualitative methodology was used and applied techniques as focus groups and interviews with users of social programs of different nature. As a result a list of rights of the community that can be summarized in was developed: right to clear and transparent information; right to participation and decision making; right to respect and recognition of the community; right to autonomy of the community; right to receive quality interventions. © 2018 Pontificia Universidad Javeriana.